2006
DOI: 10.1111/j.1467-9701.2006.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

East Asia's Anti‐dumping Problem

Abstract: East Asia accounts for a large and growing share of worldwide anti-dumping (AD) activity. East Asian countries have long been the main targets of AD actions, accounting for about one-third of all AD actions during the 1980s, more than 40 per cent of all AD actions during the 1990s, and almost 50 per cent of all AD actions in recent years. After controlling for factors that might influence filings such as the exchange rate and trade volume, it is found that East Asian countries are subject to about twice as man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…According to Prusa (2006), WTO members reported 1.441 antidumping investigations, compared to only 115 countervailing duty investigations and 61 safeguard investigations between 1995 and 2000. The dramatic rise in antidumping actions could reflect an increase in dumping activities or an increasing awareness (e.g.…”
Section: Trends Of Antidumping Actions Targeting East Asiamentioning
confidence: 99%
See 2 more Smart Citations
“…According to Prusa (2006), WTO members reported 1.441 antidumping investigations, compared to only 115 countervailing duty investigations and 61 safeguard investigations between 1995 and 2000. The dramatic rise in antidumping actions could reflect an increase in dumping activities or an increasing awareness (e.g.…”
Section: Trends Of Antidumping Actions Targeting East Asiamentioning
confidence: 99%
“…Until now, the most countries have established their own antidumping law (Figure 1) and antidumping measures has become the most popular instrument of protectionist trade policies. According to Prusa (2006), WTO members reported 1.441 antidumping investigations, compared to only 115 countervailing duty investigations and 61 safeguard investigations between 1995 and 2000. The dramatic rise in antidumping actions could reflect an increase in dumping activities or an increasing awareness (e.g.…”
Section: Trends Of Antidumping Actions Targeting East Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Using probit estimation method, Mah (2006) tried to reveal the microeconomic determinants of antidumping duties in the United States. Prusa (2006) revealed that with respect to antidumping duties East Asia is definitely treated differently than all other parts of the world, using macroeconomic variables as the determinants of the antidumping duties.…”
Section: Institutional Characteristics Of the Antidumping Duties Agai...mentioning
confidence: 99%
“…The current international trade regulations include provisions allowing the importing countries to investigate and impose the antidumping duties against the exports of the transition economies for social or political considerations. Authors such as Finger et al (1982), Moore (1992), Baldwin and Steagall (1994), Hansen and Prusa (1996), Leidy (1997), Mah (2000a), Lee and Mah (2003), Nielsen and Rutkowski (2005), and Prusa (2006) tried to reveal the determinants of antidumping duties. However, they did not consider the social and political factors such as labor standards and different degrees of democraticness as the determinants of antidumping duties.…”
Section: Introductionmentioning
confidence: 99%